Late Variscan calc-alkaline lamprophyres in the Krupka ore district, Eastern Krusne hory/Erzgebirge: their relationship to Sn-W mineralization - Stemprok,M.; Dolejs,D.; Holub,F.V. (Journal of Geosciences, 2014)
Variscan lamprophyres occur in the greisen tin-, tungsten- and molybdenum-ore district of Krupka in the Eastern Krusne hory/Erzgebirge (KHE). They belong to a bimodal dyke suite of aplites, felsic porphyries, microgranites and mafic dykes associated with late Variscan tin-bearing granites and include minettes, kersantites and spessartites, while vogesite reported earlier has not been confirmed. One altered mafic dyke is interpreted as original microdiorite. All lamprophyres are basic to intermediate rocks (47.3-56.9 wt. % SiO2) with shoshonitic to ultrapotassic composition (3.1-7.5 wt. % K2O). The high concentrations of MgO (4.7-11.4 wt. %), molar Mg/(Mg + Fe) ratios (0.56-0.74) and abundances of compatible elements (350-800 ppm Cr, 130-360 ppm Ni) indicate that lamprophyres represent primary mantle melts that underwent no or little fractionation or contamination, and high LREE/HREE ratios point to magma formation in the stability field of garnet peridotite. In addition, high contents of potassium and LILE (50-370 ppm Li, 150-920 ppm Rb, 750-3100 ppm Ba) indicate metasomatic enrichment of the upper mantle prior to partial melting. The LILE-HFSE-REE patterns indicate involvement of slab components (subducted siliciclastic and carbonate sediments). Strong enrichment in U (6-29 ppm) and Th (17-75 ppm) is another characteristic feature of lamprophyres from the Eastern KHE and elsewhere in central Europe, and it is consistent with the metasomatic transport via oxidized saline fluids from the slab to the mantle wedge. The lamprophyres in the Krupka district were variably greisenized in the vicinity of granite greisens and Sn-W hydrothermal veins and their original minerals were replaced by an assemblage of lithian phlogopite, topaz, fluorite, apatite and titanium-bearing phases. During alteration, they were strongly depleted in Na2O, CaO, Sr and Ba, moderately depleted in REE, and enriched in Li, Rb, Cs, Sn and F. By contrast, Al and Zr behaved as immobile elements and their abundances indicate overall mass loss of 10-18 % during greisenization consistent with the formation of porosity, which facilitated the hydrothermal dissolution-precipitation reactions. The spatial association of greisens and lamprophyres suggests that the greisenizing fluids migrated along similar geological structures, which were previously accessible to the mantle-derived media (melts and/or fluids). On a local scale, the lamprophyre dykes intersected by greisen veins provided geochemical or rheological barrier, which favoured the cassiterite deposition. The timing of lamprophyre dykes also indicates that the mantle metasomatism beneath the KHE area occurred before the late Variscan granitic magmas were generated.
Keywords: lamprophyres; greisenization; Li mica composition; mantle metasomatism; Krusne hory/Erzgebirge; Bohemian Massif